Liệu rằng đầu tư công nghệ thông tin và truyền thông có làm gia tăng doanh thu hoạt động dịch vụ của các ngân hàng thương mại Việt Nam - Vương Thị Hương, Giang; Lương Trần Hoàng, Hương; Nguyễn Hữu, Mạnh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
In the context of digital transformation taking place strongly, this article examines the impact of information technology and communication investment on an increase in service income at Vietnamese commercial banks in the period 2012–2020. This study uses estimations with random-effect, fixed-effect, and feasible generalized least squares for a data set of information and communication technology indicators and financial data of Vietnamese commercial banks. Research results show that information and communication technology has a positive relationship with the ratio of service revenue to the bank's total income. Further analysis shows that the impact of the technical infrastructure development and information services indexes increases the service income of commercial banks, while the human infrastructure development index reduces the service income of commercial banks in Vietnam. This paper provides some implications for income diversification strategies for Vietnamese commercial banks.
Keywords: Digital transformation; ICT; Service income; Commercial banks; Fintech